Pengaruh Citra Merek dan Keluarga Terhadap Keputusan Pembelian Sepeda Motor Suzuki di Universitas Muhammadiyah Surabaya - Ratri Amelia Aisyah (UNUSA Press, 2017)
Competition in the development of business in the era of globalization requires companies to be able to act quickly and appropriately in the face of competition in the business environment is very dynamic and full of uncertainty. The study aims to assess Brand Image of Suzuki and Family as an effort to influence Purchase Decision Making. The research conducted a survey respondents to 100 students of Muhammadiyah University in Surabaya. Analysis techniques used to examine the relationship among the variables using multiple linear regression. The results of a study showed that Brand Image has direct and significantly influence on Purchase Decision Making and the result showed that Family has direct and significantly influence on purchasing decision making on Suzuki.